PENGARUH PENGELUARAN KONSUMSI PEMERINTAH DAN PENGELUARAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Hayati, Jurni; Hanapia, Asep Yusup; Ramadhan, Rifky Wahyu (Universitas Bengkulu, 2024)
Economic growth depends on the amount of public consumption expenditure, government consumption expenditure, investment spending, and the value of net exports. The trend of economic growth in Indonesia during the 2011-2023 period declined, even in 2020 it experienced a drastic decline to minus 2.07 percent because of Covid-19 Pandemic. To increase Indonesia's economic growth, the government has implemented policies that can encourage an increase in household consumption spending by allocating funds for social protection and government consumption spending by increasing funds for spending on ministries/agencies. This study aims to analyze the effect of government consumption spending and investment spending on economic growth in Indonesia. The analytical method used in this study is multiple linear regression analysis and the data used is time series data for the years 2011-2023. Based on the results of the study, partially, the variable of government consumption expenditure (NPPKP) has no effect on economic growth in Indonesia, while investment expenditure (NPPM) has a positive and significant effect on economic growth in Indonesia. Then simultaneously, the government consumption expenditure variable (NPPKP) and the investment expenditure variable (NPPM) have a significant effect on economic growth in Indonesia. Based on the determination coefficient test yields an adjusted R-square value of 0.67, indicating that the variables can account for approximately 67 percent and 33 percent of the economic growth variable, respectively, through other variables not included in the analysis. Keywords: Economic Growth, Government Consumption Expenditure, Investment Expenditure Abstrak Pertumbuhan ekonomi bergantung pada besaran belanja konsumsi publik, belanja konsumsi pemerintah, belanja investasi, dan nilai ekspor bersih. Tren pertumbuhan ekonomi Indonesia selama periode 2011-2023 menurun, bahkan pada tahun 2020 mengalami penurunan drastis menjadi minus 2,07 persen karena Pandemi Covid-19. Untuk meningkatkan pertumbuhan ekonomi Indonesia, pemerintah telah menerapkan kebijakan yang dapat mendorong peningkatan belanja konsumsi rumah tangga dengan mengalokasikan dana untuk perlindungan sosial dan belanja konsumsi pemerintah dengan meningkatkan dana untuk belanja kementerian/lembaga. Penelitian ini bertujuan untuk menganalisis pengaruh belanja konsumsi pemerintah dan belanja investasi terhadap pertumbuhan ekonomi di Indonesia. Metode analisis yang digunakan dalam penelitian ini adalah analisis regresi linier berganda dan data yang digunakan adalah data deret waktu tahun 2011-2023. Berdasarkan hasil penelitian, secara parsial Belanja Pemerintah (NPPKP) tidak berpengaruh terhadap pertumbuhan ekonomi Indonesia, sedangkan belanja investasi berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi, kemudian secara simultan variabel pengeluaran konsumsi pemerintah (NPPKP) dan variabel pengeluaran investasi (NPPM) berpengaruh signifikan terhadap pertumbuhan ekonomi di Indonesia. Berdasarkan uji koefisien determinasi diperoleh nilai Adjusted R-square sebesar 0,67, yang menunjukkan bahwa variabel pengeluaran konsumsi pemerintah (NPPKP) dan variabel pengeluaran investasi (NPPM) mampu menjelaskan variabel pertumbuhan ekonomi sekitar 67 persen dan 33 persen dijelaskan oleh variabel lain diluar model. Kata Kunci: Pertumbuhan Ekonomi, Belanja Konsumsi Pemerintah, Belanja Investasi